2008
DOI: 10.1186/1757-1626-1-67
|View full text |Cite
|
Sign up to set email alerts
|

Cross-system effects of dysphagia treatment on dysphonia: a case report

Abstract: Traditionally, treatment of dysphagia and dysphonia has followed a specificity approach whereby treatment plans have focused on each dysfunction individually. Recently however, a therapeutic cross-system effect has been proposed between these two dysfunctions. At least one study has demonstrated swallowing improvement in subjects who completed a dysphonia treatment program. However, we are unaware of any evidence demonstrating the converse effect. In this paper, we present a case-report of a 74 year old male w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 8 publications
0
21
0
9
Order By: Relevance
“…A few published reports have also documented improvement in vocal function. LaGorio, Carnaby-Mann, & Crary [4] reported an improvement in maximum phonation time and pitch range in a patient who received TES in conjunction with traditional dysphagia therapy. They noted that the improvement in vocal function likely reflected the combined effect of TES and swallowing exercises e.g.…”
Section: Introductionmentioning
confidence: 97%
“…A few published reports have also documented improvement in vocal function. LaGorio, Carnaby-Mann, & Crary [4] reported an improvement in maximum phonation time and pitch range in a patient who received TES in conjunction with traditional dysphagia therapy. They noted that the improvement in vocal function likely reflected the combined effect of TES and swallowing exercises e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Actually, vocal fold instability is closely related to laryngeal muscle weakness, and many treatments can be applied for strengthening of such muscles, among which laryngopharyngeal NMES has been vigorously researched in the clinical setting [6781011]. In the present study, the NMES group showed a significant group-by-time interaction with regard to jitter, which represents the frequency perturbation of vocal fold vibration.…”
Section: Discussionmentioning
confidence: 62%
“…Collectively, these studies showed emerging evidence in utilizing NMES on patients with vocal fold bowing, unilateral laryngeal nerve paresis, and vocal nodules . Regarding the use of NMES in head and neck cancer patients, only a single case report was found in the literature supporting its use for vocal rehabilitation . In this study, following 15 days of NMES paired with effortful swallow technique, the post chemoradiation patient with tongue squamous cell carcinoma showed improvement in maximum phonation time and highest attainable pitch.…”
Section: Introductionmentioning
confidence: 65%
“…In this study, following 15 days of NMES paired with effortful swallow technique, the post chemoradiation patient with tongue squamous cell carcinoma showed improvement in maximum phonation time and highest attainable pitch. The authors speculated that NMES increased vocal fold tension and promoted glottal closure, thus reducing vocal impairment …”
Section: Introductionmentioning
confidence: 99%